Effects of acetylcholine and cholinergic antagonists on the activity of nucleus of the solitary tract neurons - Furuya, Werner I. [UNESP]; Colombari, Eduardo [UNESP]; Ferguson, Alastair V.; Colombari, Debora S. A. [UNESP] (Elsevier B.V., 2017)
Previously we have demonstrated that microinjection of acetylcholine (ACh) into the intermediate nucleus of the solitary tract (iNTS) induced sympatho-inhibition combined with a decrease in the phrenic nerve activity (PNA), whereas in the commissural NTS (cNTS), ACh did not change sympathetic nerve activity (SNA), but increased the PNA. In view of these demonstrated distinctive effects of ACh in different subnuclei of the NTS the current studies were undertaken to examine, using patch clamp techniques, the specific effects of ACh on the excitability of individual neurons in the NTS, as well as the neuropharmacology of these actions. Coronal slices of the brainstem containing either cNTS or iNTS subnuclei were used, and whole cell patch clamp recordings obtained from individual neurons in these two subnuclei. In cNTS, 58% of recorded neurons (n = 12) demonstrated rapid reversible depolarizations in response to ACh (10 mM), effects which were inhibited by the nicotinic antagonist mecamylamine (10 mu M), but unaffected by the muscarinic antagonist atropine (10 mu M). Similarly, bath application of ACh depolarized 76% of iNTS neurons (n = 17), although in this case both atropine and mecamylamine reduced the ACh-induced depolarization. These data demonstrate that ACh depolarizes cNTS neurons through actions on nicotinic receptors, while depolarizing effects in iNTS are apparently mediated by both receptors. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Nicotinic receptors; Muscarinic receptors; Acetylcholine; Patch clamp